Social Semiotics Evaluation of English One by Gender - Nesa Nabifar; Mir Saeid Baghermousavi (Studies in English Language and Education, 2015)
Textbooks receive focal attention in every educational setting. In 2013, the English text books used in Iranian schools were changed and new books, the Prospect series, were introduced. The older English text books are not used for teaching anymore. One of these was English One which was used for teaching the first grade at junior high school. As far as the researchers know, there was no previous research using this book in terms of gender from a semiotic point of view. Therefore, the researchers tried to investigate it in terms of social semiotics as defined by Kress and van Leeuwen (2006). Their findings showed that males are more often present in the images, and both genders are seen as collaborating with the readers of this book. Their findings also showed that both genders are trying to encourage the readers toward establishing communication by more often showing gaze towards each other in the images. This study has implication for students of linguistics, for course designers and for English teachers as well.